Exploiting halido ligands to control nucleation pathways and Pt⋯Pt interactions in supramolecular co-polymerizations. Issue 88 (19th October 2022) - Matern, Jonas; Fernández, Zulema; Fernández, Gustavo
Abstract : We exploit halogen effects to tune metal–metal interactions, nucleation pathways and hetero-seeded growth in supramolecular copolymerizations. Abstract : We use different halido ligands to tune metal–metal interactions, nucleation pathways and hetero-seeded growth in supramolecular copolymerizations.